62.3k views
5 votes
Solve by using the quadratic formula:
x² - 6x + 7-O

User JPJens
by
4.7k points

2 Answers

2 votes

Explanation:

Hey there!!

The equation is;


{x}^(2) - 6x + 7 = 0

Now, Comparing it with ax^2 + bx + c = 0. we get;

a = 1, b= -6 and c = 7

Use quadratic formula.


x = \frac{ - b + - \sqrt{ {b}^(2) - 4ac} }{2a}

Put all values.


x = \frac{ + 6 + - \sqrt{( { - 6)}^(2) - 4 * 1 * 7} }{2 * 1}

Simplify them.


x = (6 + - √(36 - 28) )/(2)


x = ( 6 + - √(8) )/(2)


x = (6 + - 2 √(2) )/(2)

Taking positive (+).


x = (6 + 2 √(2) )/(2)

Simplifying them.


x = (2(3 + √(2) ))/(2)


x = 3 + √(2)

Now, Taking negative (-).


x = (6 - 2 √(2) )/(2)

Simplifying them.


x = (2(3 - √(2) ))/(2)


x = 3 - √(2)

Therefore the answer is;


x = 3 + √(2) \: and \: 3 - √(2)

Hope it helps...

User Jonathan Sayce
by
5.1k points
3 votes

Answer:

it is x=7

x=-1

Explanation:

i using the quadratic formula

User Monic
by
4.9k points